Implementasi Program Pendidikan Karakter Model AIA KAWA di Kelas VI SDS Al-Azhar Bukittinggi - Asri, Rafiqa Witri; Ilmi, Darul; Mulia, Ezi; Simbolon, Ali Mustopa Yakub; Syafitri, Aisyah; Pilbahri, Sarah (LP2M Universitas Islam Ahmad Dahlan, 2024)
This research aims to find out and detect the characteristics of students with special needs so that educational services for them can be carried out according to what they need. The approach used is qualitative case study by collecting data in the form of interviews, observation and documentation. The research subjects were the Principal, Grade VI teacher and teachers at SDS Al-Azhar Bukittinggi. This study found a programme that is run for every student, especially students with special needs in the form of programmes such as: (1) Father and Mother's heartfelt letter, (2) a piece of story, (3) character card, (4) work exhibition and (5) talent development. The existence of these programmes, it is clear that the character of students has become more courageous and confident and responsible for themselves. From these programmes, there are clear results such as (1) Students become more confident in participating in education and learning programmes inside and outside the classroom, (2) Increased concentration and seriousness of students in learning so that they are more active in competing in learning, (3) Increased student honesty and more sportive in admitting mistakes to take responsibility, (5) Increased mutual respect for others and respect for teachers and parents, (6) Increased student creativity in producing work and (7) Achieved brilliant achievements by regular students and students with special needs.